PELATIHAN TEKNIK DASAR RENANG GAYA DADA PADA SISWA SMA NEGERI I TOMOHON - Mesak. A. S. F. Rambitan (LPPM UNIMA, 2021)
Based on the results of observations in the field of the many problems in this training activity, the problem is how to develop the skills of students about breaststroke swimming. The lack of development of student achievement in this sport is caused, among others, by the lack of knowledge and understanding of students about breaststroke swimming and the lack of interest and talent development of students about the sport. The purpose of the training activities is to educate students as beginner athletes to be able to master swimming skills, especially breaststroke swimming. The target audiences in this service are students of SMA Negeri I Tomohon, whose achievements are very potential to be fostered and developed. Based on the results of the evaluation of activities, it can be concluded that this training has a positive impact and opens the participants' insight to be able to improve mastery of swimming skills.